Analisis Keputusan Pembelian Konsumen dari Sisi Normatif dan Informatif Pada Hypermart Cibubur Junction, Jakarta Timur - Ade Onny Siagian; Trisna Fajar Prasetyo (Yayasan Literasi Sains Indonesia, 2022)
The purpose of this study was to analyze the factors that influence community purchasing decisions in terms of normative and informative marketing that is always changing and developing in the Giant Pamulang supermarket, South Tangerang. This study uses descriptive qualitative method using observation, interviews and questionnaires. The sample in this study is a buyer subscription at Hypermart Cibubur supermarket, East Jakarta. The form of analysis focuses on normative and informative factors and a combination of both in the process of purchasing decisions in supermarkets related to products in the form of consumer goods. From the observations, the decision to buy the community and consumers of supermarkets Hypermart Cibubur, East Jakarta, is influenced by several factors, including: consumers are more concerned about product quality and start paying attention to the moral and social responsibility of the company, lifestyle changes due to an increase in the amount of income received, education the better, and also because of changes in cultural values and the location of supermarkets that are not far from the residence and physical facilities of supermarkets.